ANÁLISE DE SENSIBILIDADE DO METAMODELO DA ETIQUETAGEM BRASILEIRA: EDIFICAÇÕES COMERCIAIS - Bavaresco, Mateus; Mazzaferro, Leonardo; Melo, Ana Paula; Lamberts, Roberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The main objective of this study is to verify the relation between input parameters and thermal load output of a metamodel, based on sensitivity analysis. The study is based on a metamodel developed to assess the thermal load of commercial buildings. One commercial typology, located in the cities of São Paulo, Belém and Curitiba was adopted. Maximum and minimum values of input data were determined to represent the different combinations among the Brazilian commercial buildings. The analysis was carried out by changing one parameter per time, according to a base case pre-determined. The sensitivity analysis was able to describe the influence of each parameter on the metamodel output cooling thermal load. The results show that the metamodel was able to describe the relation between inputs and output parameter. Therefore, it was observed that, depending on the case and climate analyzed, as using high values of overall heat transfer coefficient in the walls can help to dissipate the internal heat gain to the exterior, minimizing the cooling thermal load.